Analisis Kitab Al-'Arabiyyah li Al-Nasyi’īn dalam Pembelajaran Mahārah Qirā’ah di Pondok Pesantren - Muzayanah, Ainiyatul; Setiyawan, Agung; Mansur, Nuryani; Putri, Devilia Kharisma (Study Program of Arabic Language Teaching, 2025)
This study aims to analyse the contribution of the book Al-‘Arabiyah li An-Nāsyi’īn in developing the Reading skills of students at the Al-Arifin Denanyar Islamic Boarding School in Jombang. The study uses a qualitative case study approach. The primary data sources are from the book Al-‘Arabiyah li An-Nāsyi’īn, supported by curriculum documents, observations of the learning process, and interviews with teachers and students. Data collection techniques include literature study, non-participatory observation, and semi-structured interviews, while data analysis is conducted through content analysis. The results showed that the Al-‘Arabiyah li An-Nāsyi’īn textbook has a systematic and gradual content structure, in accordance with the principles of Arabic textbook development, and is relevant to linguistic, communicative, and cultural competencies. In addition, the teaching methods used are communicative and contextual, thereby supporting more meaningful Reading learning. The use of this book has a positive impact on text comprehension, strengthening Arabic literacy, fostering independent learning, and shaping the character of santri through Islamic values. Thus, Al-‘Arabiyah li An-Nāsyi’īn can be considered an effective textbook in supporting the development of maharatul qirā’ah santri in Islamic boarding schools.